Oncolytic activity of Newcastle disease virus strain AF2240 in hypoxic cancer cells - Abd Aziz, Noraini (2018)
Solid tumors have different microenvironment that can influence the capability of cancer treatments. Cancer cells in low oxygen condition or hypoxia, present an obstacle as they are more resistant towards chemotherapy and radiotherapy. The use of oncolytic viruses as therapeutic agent has demonstrated promising results making it an ideal approach to treat cancer cells. Newcastle disease virus (NDV) is an oncolytic virus that has specificity in targeting tumor cells over normal cells. Despite its potential, the exact mechanism of its oncolysis in hypoxic cancer cells remains unknown. In the present study, the oncolytic activity of NDV in hypoxic cancer cells was investigated. Various cancer cell lines such as osteosarcoma (Saos-2), breast carcinoma (MCF-7) and fibrosarcoma (HT1080) cells were infected with NDV under normoxic or hypoxic conditions. Following NDV infection, molecular, proteomic, immunological and biochemical techniques were performed. Data obtained in this study showed that NDV was capable to infect and replicate in hypoxia tumor microenvironment similar to normoxia. This was confirmed by the equivalent level of NP viral protein expressed in normoxic and hypoxic conditions of Saos-2, MCF-7 and HT1080 cells. The amount of NP viral protein detected in the infected cells was correlated with the production of the viral progeny. It was observed that NDV replicates in hypoxic cancer cells to levels comparable to normoxic cells, leading to induction in cytopathic effects which subsequently caused cell death. MCF-7 cells which displayed better replication upon NDV infection resulted in more cytotoxicity than in Saos-2 and HT1080 cells. These data provide evidence that NDV was able to adapt and exhibit an oncolytic capacity in hypoxic tumor cells in a manner that is equivalent to the normoxic tumor cells and was cell type specific. Hypoxic tumor cells negatively affect therapeutic outcome by overexpressing pro-survival genes under the control of the hypoxia-inducible factor (HIF). HIF-1 is a heterodimer transcriptional factor consisting of a regulated α (HIF- 1α) and constitutive β subunit (HIF-1β). Overexpression of HIF contributes to an aggressive malignancy, which is associated with chemoresistance and radioresistance. In the present study, the effects of NDV infection on HIF-1α in cancer cells were examined. Data obtained showed that a velogenic NDV infection diminished hypoxiainduced HIF-1α accumulation, leading to a decreased activation of its downstream target gene, carbonic anhydrase 9 (CA9). This NDV-induced down regulation of HIF 1α occurred post-translationally and was partially abrogated by proteasomal inhibition. The process appeared to be independent of the tumor suppressor protein, p53. Apart from the ability of NDV in targeting hypoxic cancer cells and HIF-1α, the significance of hypoxia in the antiviral response towards NDV infection was also evaluated in this study. Data obtained showed that IFN-β is the principal antiviral factor produced by cells in response to NDV infection. Hypoxic condition was observed to minimally affect the levels of IFN-β production in MCF-7 cells, but not in Saos-2 and HT1080 cells. NDV infection in hypoxic conditions did not drastically alter the level of IFN-β production including STAT proteins. In addition, NDV induced IFN-β secretion results in increased levels of total STAT1 and STAT1 phosphorylation proteins leading to cell death. In summary, this study demonstrated that NDV infection down regulates HIF-1α and induced cell death in hypoxic tumor cells comparable to normoxic with the involvement of IFN-β signalling. These findings also help in improving the existing data regarding the efficiency of NDV as a promising therapeutic agent to infect and eliminate various types of cells in different tumor microenvironments, particularly in hypoxic cancer cells.